Photoacoustic and ultrasound (PAUS) dermoscope with high sensitivity and penetration depth by using a bimorph transducer. Issue 9 (6th July 2020) - Wang, Zhiyang; Yang, Fei; Ma, Haigang; Cheng, Zhongwen; Yang, Sihua
Abstract: A bimorph transducer was proposed to improve the detection sensitivity and imaging depth of photoacoustic and ultrasound (PAUS) dermoscope. By applying the bimorph transducer, the imaging depth and sensitivity of PAUS dermoscope were enhanced by simultaneously improving excitation efficiency and reception bandwidth. The integrated design of the imaging head of the dermoscope makes it highly convenient for detecting human skin. The PAUS imaging performance was demonstrated via visualizing subcutaneous tumor and depicting full structures of different skin layers from epidermis to subcutaneous tissue. The results confirm that the dermoscope with the bimorph transducer is well suited for PA and US dual‐modality imaging, which can provide multi‐information for skin disease. Abstract : In this study, a bimorph transducer is proposed to improve the detection sensitivity and imaging depth of photoacoustic and ultrasound (PAUS) dermoscope. By applying the bimorph transducer, the imaging depth and sensitivity of PAUS dermoscope were enhanced by simultaneously improving excitation efficiency and reception bandwidth. The integrated design of the imaging head of the dermoscope makes it highly convenient for detecting human skin. The results confirm that the dermoscope with the bimorph transducer is well suited for PA and US dual‐modality imaging, which can provide multi‐information for skin disease.